2020
DOI: 10.47276/lr.91.4.367
|View full text |Cite
|
Sign up to set email alerts
|

Depression and anxiety in people affected by leprosy and lymphatic filariasis: a cross-sectional study in four States in India

Abstract: Individual studies reported high levels of depression and anxiety among people affected with leprosy and lymphatic filariasis (LF), but they are often too small for a reliable comparison of prevalence mental ill health or its risk. The current study explores prevalence and risk factors of depression and anxiety within a large programme of a non-governmental organisation in India. Methods: In a cross-sectional survey, we administered face-to-face Washington Group extended questions for Mental Health among lepro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 36 publications
0
4
1
Order By: Relevance
“…This proportion of respondents who were depressed from the result of this study is higher than what was obtained from a study in Sokoto, Nigeria where 47.7% of the people with leprosy had psychiatric disorders [15]. Studies in India have indicated the range of depressive disorders from 30-53% for persons affected by leprosy [22][23][24][25]. The study also revealed that very high proportion of respondents 79.4% were found to have anxiety disorders.…”
Section: Discussioncontrasting
confidence: 61%
See 1 more Smart Citation
“…This proportion of respondents who were depressed from the result of this study is higher than what was obtained from a study in Sokoto, Nigeria where 47.7% of the people with leprosy had psychiatric disorders [15]. Studies in India have indicated the range of depressive disorders from 30-53% for persons affected by leprosy [22][23][24][25]. The study also revealed that very high proportion of respondents 79.4% were found to have anxiety disorders.…”
Section: Discussioncontrasting
confidence: 61%
“…In a study in India that involved persons affected by leprosy who presented in the out-patient department of a hospital, 10% of them had anxiety disorders [ 23 ]. In a study that included persons affected by leprosy and lymphatic filariasis, about half of them reported episodes of depression and anxiety [ 24 ]. In another study in India, 19% of persons affected by leprosy were found to have anxiety disorders [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…This is similar to the findings reported in India, where participants affected by leprosy reported a higher intensity of depression and anxiety. 32 The results also showed that stigma exists among persons affected by NTDs, especially in getting a job, feeling pity and ashamed, and avoidance by other people. The results of the current study are consistent with studies in Bangladesh 9 and Brazil 33 using the WHOQOL-BREF, which found that people with leprosy had significantly poorer QOL than controls.…”
Section: Discussionmentioning
confidence: 92%
“…For instance, a higher disability grade can result in poorer mental well-being, perceived stigma and QOL. 32 , 34 , 37 Our study did not measure disability grade among the patients. The previous study largely used the Dermatology Life Quality Index to measure the QOL of patients affected by leprosy and LF, which limited the comparison of QOL observed in this study.…”
Section: Discussionmentioning
confidence: 97%
“… 1–4 A study in India has demonstrated that approximately one-half of the people affected by leprosy or LF experience depression or anxiety. 2 Peer support has been suggested as a promising strategy to address these psychosocial issues, as it has been shown to be effective in reducing stigma and increasing social participation in the field of leprosy. 5 , 6 …”
Section: Introductionmentioning
confidence: 99%